IMPLEMENTATION OF E-COMMERCE AND ACCOUNTING INFORMATION SYSTEM TOWARDS SUCCESSFUL SMES PERFORMANCE - Sari, Wilda; Setiawan, Aris; Reswari, Rianti Ardana (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to evaluate the impact of accounting information systems and e-commerce usage on the success of SMEs and to identify the factors influencing SME owners in adopting these systems. A descriptive quantitative approach was employed, with data collected through questionnaires or surveys. The research population consisted of SMEs in Pontianak City, and the sample was selected using a purposive sampling technique. Data analysis was conducted using regression analysis and processed with SPSS version 23. The results indicated that the adoption of accounting information systems and e-commerce has a positive and significant effect on SME success. E-commerce contributes to expanding market share and increasing public awareness of SME products, while accounting information systems (AIS) assist business owners in making informed decisions. Factors influencing SME success in utilizing e-commerce and AIS include the availability of technological infrastructure, human resource competence, and the business owners' attitudes toward technology.